Obstetrical brachial plexus injury (OBPI): Canada's national clinical practice guideline. Issue 1 (27th January 2017) - Coroneos, Christopher J; Voineskos, Sophocles H; Christakis, Marie K; Thoma, Achilleas; Bain, James R; Brouwers, Melissa C
Abstract : Objective: The objective of this study was to establish an evidence-based clinical practice guideline for the primary management of obstetrical brachial plexus injury (OBPI). This clinical practice guideline addresses 4 existing gaps: (1) historic poor use of evidence, (2) timing of referral to multidisciplinary care, (3) Indications and timing of operative nerve repair and (4) distribution of expertise. Setting: The guideline is intended for all healthcare providers treating infants and children, and all specialists treating upper extremity injuries. Participants: The evidence interpretation and recommendation consensus team (Canadian OBPI Working Group) was composed of clinicians representing each of Canada's 10 multidisciplinary centres. Outcome measures: An electronic modified Delphi approach was used for consensus, with agreement criteria defined a priori. Quality indicators for referral to a multidisciplinary centre were established by consensus. An original meta-analysis of primary nerve repair and review of Canadian epidemiology and burden were previously completed. Results: 7 recommendations address clinical gaps and guide identification, referral, treatment and outcome assessment: (1) physically examine for OBPI in newborns with arm asymmetry or risk factors; (2) refer newborns with OBPI to a multidisciplinary centre by 1 month; (3) provide pregnancy/birth history and physical examination findings at birth; (4) multidisciplinary centres should include a therapist and peripheral nerve surgeon experienced with OBPI; (5) physical therapy should be advised by a multidisciplinary team; (6) microsurgical nerve repair is indicated in root avulsion and other OBPI meeting centre operative criteria; (7) the common data set includes the Narakas classification, limb length, Active Movement Scale (AMS) and Brachial Plexus Outcome Measure (BPOM) 2 years after birth/surgery. Conclusions: The process established a new network of opinion leaders and researchers for further guideline development and multicentre research. A structured referral form is available for primary care, including referral recommendations.